Case Report: A Rare Case of Isolated Pulmonary Valve Infective Endocarditis Complicated by Bloody Pleural Effusion from Septic Pulmonary Embolism - Buangoen, Anchalee (Princess of Naradhiwas University Journal, 2022)
Isolated pulmonary valve endocarditis (PVE) is an extremely rare form of right-sided infective endocarditis (RSIE) in adults. PVE tends to affect younger patients and most are male. The majority of cases involve a tricuspid valve. Intravenous drug users are at increased risk for developing RSIE. Diagnosis can be challenging because of non-specific symptoms (fever, dyspnea, hemoptysis, and pleuritic chest pain) and the difficulty of detection by physical examination and echocardiography. We describe a case of PVE in a 40-year-old male, who was a current intravenous drug user. He presented with fever, dyspnea, and acute respiratory failure, complicated with bloody pleural effusion from septic pulmonary emboli. The chest radiography showed pleural effusion. Diagnostic thoracocentesis showed sterile bloody pleural effusion. Septic pulmonary embolism in both lungs was found from a computed tomography scan of the chest. Transthoracic echocardiography revealed large vegetation with pulmonic insufficiency. Blood cultures showed the presence of Staphylococcus aureus (MSSA). Cloxacillin was administered intravenously, respectively. The patient still had a high-grade fever, repeated septic pulmonary embolism and unresponsiveness to antibiotics within 4 weeks, thus this case was referred for cardiothoracic surgery for pulmonary valve replacement.